Paper-based solution sampling coupled with potentiometric ion sensors - Ding, Ruiyu (Nanyang Technological University, 2021)
The determination of heavy metals and clinically relevant ions is vital to maintain environmental quality and human health. In some situations, the samples do not contain a sufficient volume of the liquid to be collected for the analysis and to be measured using standard analytical methods. Potentiometric analysis based on ion-selective electrodes (ISEs) is performed by simple, portable and low-cost equipment, which can be used to monitor real-time ion activity in small-volume samples. To wick and deliver to the electrodes by capillarity action micro volumes of sample solutions with high solid-to-liquid ratios, as well as to avoid the electrodes being mechanically damaged by a rough surface of some samples/sampling surfaces, paper substrates were previously investigated as microfluidic sampling devices. However, the application of paper-based sampling coupled with potentiometric cell in heavy metal sensing was characterised with super-Nernstian response, thus was deemed as not suitable for reliable ion determination. Additionally, the ISEs and reference electrodes (REs) are prone to biofouling when used in the clinical samples, causing errors in ion determination. Lastly, the commonly used reference electrode Ag/AgCl/3M KCl is not the most suitable electrode for this particular application, namely: it is bulky and requires refilling the internal reference solution. In this work, commercial crystalline membrane solid-state and solid-contact ISEs were used to investigate the possibility to facilitate paper-based microfluidic solution sampling coupled with potentiometric sensors for the ion determination in various environmentally (containing Cd2+, Pb2+ and pH) and clinically relevant (containing K+, Na+, Cl–) samples. To eliminate the unfavourable effects, different paper substrate pre-treatments were investigated, namely: (i) modifications of paper substrates with primary or interfering ions and acidification of paper substrates to chemically bind the active groups on the paper, thus avoid subsequent paper substrate interactions with metal ions in the sample solution; (ii) modifications of paper substrates by gold nanoparticles (AuNPs) to selectively remove/diminish transport of proteins from the clinical samples. Moreover, a new design of the solid-state paper-based reference electrode was investigated with the paper-based potentiometric sensors to provide constant and stable potential without refilling the internal reference solution. Lastly, the microfluidic sponge-based sampling was developed and studied as a novel sampling and sample handling method to serve as an alternative for microfluidic paper-based solution sampling, allowing measurements of heavy metals without prior modification of the sampling substrate.